2005
DOI: 10.14341/osteo200512-6
|View full text |Cite
|
Sign up to set email alerts
|

IZMENENIYa KOSTNOY TKANI ChELOVEKA V KOSMIChESKOM POLETE II. NEKOTORYE ZAKONOMERNOSTI I OSOBENNOSTI

Abstract: No 1/2005 Остеопороз и остеопатии2 ВВЕДЕНИЕ В предыдущей статье [14] были описаны основ-ные феномены в костной ткани человека, сопро-вождающие его полет на орбитальной станции (ОС) "МИР" длительностью 5-7 месяцев. Одним из основных выводов было доказательство того факта, что потери костной массы в трабекулярных структурах костей нижней половины скелета за данный период времени в среднем по группе не создают ситуации, которую по принятому ВОЗ регламенту можно было бы квалифицировать как остеопороз. В целом сово… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Previously an association between bone loss and bone position relative to gravitational vector was identified in human space travellers (Oganov et al 2005;Stavnichuk et al 2020), where bone loss was most pronounced in lower limbs and bone gain was identified in the upper skeleton. We also demonstrated potential differences between the distal and axial regions in rodents (Fu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously an association between bone loss and bone position relative to gravitational vector was identified in human space travellers (Oganov et al 2005;Stavnichuk et al 2020), where bone loss was most pronounced in lower limbs and bone gain was identified in the upper skeleton. We also demonstrated potential differences between the distal and axial regions in rodents (Fu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Included articles described studies in rats (18/30) (Davis et al 1998;Hatton et al 2002;Keune et al 2015;Kleber et al 1989;Prokhonchukov et al 1978a;Prokhonchukov et al 1977;Prokhonchukov et al 1978b;Roberts et al 1987;Rosenberg et al 1984;Savostin-Asling 1978;Simmons et al 1990a;Simmons et al 1990b;Simmons et al 1981a;Simmons et al 1980;Simmons et al 1981b;Simmons et al 1983;Tran Van et al 1981;Volozhin et al 1989), mice (6/30) (Dadwal et al 2019;Dagdeviren et al 2018;Ghosh et al 2016;Macaulay et al 2017;Maupin et al 2019;Zhang et al 2013), and humans (6/30) (Grigoriev et al 1998;Miyamoto et al 1998;Oganov 2003;Oganov et al 2005;Oganov et al 1992;Shigematsu et al 1997). The most studied hard structures within the skull were the mandible, calvaria and the lower incisors (Fig.…”
Section: Overview Of Relevant Literaturementioning
confidence: 99%
See 3 more Smart Citations